Cloning and Characterisation of (R)-3-hydroxyacyl-acyl Carrier Proteincoenzyme A Transferase Gene (phaG) from Pseudomonas sp. USM 4-55 - Hasni Arsad; Kumar Sudesh; Nazalan Najimudin; Tengku Sifzizul Tengku Muhammad; Habibah Wahab; Mohd. Razip Samian (Tropical Life Sciences Research, 2009)
The (R)-3-hydroxyacyl-ACP-CoA transferase catalyses the conversion of (R)-3- hydroxyacyl-ACP to (R)-3-hydroxyacyl-CoA derivatives, which serves as the ultimate precursor for polyhydroxyalkanoate (PHA) polymerisation from unrelated substrates in pseudomonads. PhaG was found to be responsible for channelling precursors for polyhydroxyalkanoate (PHA) synthase from a de novo fatty acid biosynthesis pathway when cultured on carbohydrates, such as glucose or gluconate. The phaG gene was cloned from Pseudomonas sp. USM 4-55 using a homologous probe. The gene was located in a 3660 bp Sal I fragment (GenBank accession number EU305558). The open reading frame (ORF) was 885 bp long and encoded a 295 amino acid protein. The predicted molecular weight was 33251 Da, and it showed a 62% identity to the PhaG of Pseudomonas aeruginosa. The function of the cloned phaG of Pseudomonas sp. USM 4- 55 was confirmed by complementation studies. Plasmid pBCS39, which harboured the 3660 bp Sal I fragment, was found to complement the PhaG-mutant heterologous host cell, Pseudomonas putida PhaGN-21. P. putida PhaGN-21, which harboured pBCS39, accumulated PHA that accounted for up to 18% of its cellular dry weight (CDW). P. putida PhaGN-21, which harboured the vector alone (PBBR1MCS-2), accumulated only 0.6% CDW of PHA. Enzim (R)-3-hydroxyacyl-ACP-CoA transferase merupakan enzim pemangkin penukaran (R)-3-hydroxyacyl-ACP kepada terbitan (R)-3-hydroxyacyl-CoA yang berfungsi sebagai substrat untuk pempolimeran polyhydroxyalkanoat (PHA) daripada substrat tidak berkaitan dalam pseudomonads. PhaG merupakan enzim yang bertanggungjawab menyalurkan substrat untuk enzim polyhydroxyalkanoat (PHA) sintase melalui laluan biosintesis de novo asid lemak apabila karbohidrat seperti glukosa atau glukonat digunakan dalam kultur pertumbuhan. Gen phaG telah diklon daripada Pseudomonas sp. USM 4-55 menggunakan kaedah prob homolog. Gen phaG terletak di dalam rantaian DNA Sal I bersaiz 3660 bp (nombor capaian GenBank EU305558). Open reading frame (ORF) phaG ialah 885 bp DNA yang mengekod 295 asid amino. Berat molekul anggaran ialah 33251 Da dan ia menunjukkan 62% identiti terhadap PhaG daripada Pseudomonas aeruginosa. Aktiviti enzim PhaG daripada Pseudomonas sp. USM 4-55 disahkan melalui ujikaji komplementasi. Plasmid pBCS39 yang mengandungi rantaian DNA Sal I 3660 bp menunjukkan aktiviti enzim PhaG apabila dimasukkan ke dalam sel perumah phaGmutant strain Pseudomonas putida PhaGN-21. P. putida PhaGN-21 yang membawa plasmid pBCS39 menghasilkan PHA sehingga 18% berat kering sel (CDW). P. putida PhaGN-21 yang membawa vektor (PBBR1MCS-2) hanya menghasilkan 0.6% CDW PHA.